FE evaluation of effect of groove geometry on roller and hydraulically expanded joint strength. (9th June 2009) - Al-Aboodi, A.S.; Merah, Nesar; Shuaib, Abdel Rahman N.; Al-Nassar, Yaagoub
The grooves machined in heat exchanger tube holes tend to improve the strength of tube-tubesheet joints and provide additional locking against leakage. The present work investigates the effect of tubesheet groove geometry on the contact stress of roller expanded and hydraulically expanded tube to tubesheet joints. The configuration of the geometry of the tube bores are varied with respect to its position, width, depth and spacing between grooves. The results of the study indicate that the effect of increasing groove width was to increase interfacial residual contact stress in hydraulically expanded joints while it has the effect of decreasing the pressure in roller expanded joints. On the other hand, groove depth, spacing and location have no significant effect for both hydraulic and roller tube expansion methods; though the residual contact stress is higher for roller expansion than for hydraulic expansion.